Planning for Motherhood: Fertility Attitudes, Desires And Intentions Among Women with Disabilities. Issue 4 (10th September 2014) - Shandra, Carrie L.; Hogan, Dennis P.; Short, Susan E.
<x xml:space="preserve">Abstract</x> CONTEXT An estimated 10% of U.S. women of reproductive age report a current disability; however, the relationship between disability, motherhood attitudes and fertility intentions among these women is largely unknown. METHODS Data from the 2006–2010 National Survey of Family Growth were used to examine attitudes toward motherhood and fertility intentions among 10, 782 U.S. women aged 15–44. A series of regression models assessed, separately for mothers and childless women, associations between disability status and women's attitudes and intentions. RESULTS Women with and without disabilities held similar attitudes toward motherhood. Among women without children, women with and without disabilities were equally likely to want a child and equally likely to intend to have one. However, childless women with disabilities who wanted and intended to have a child were more likely to report uncertainty about those intentions than were childless women without disabilities (odds ratio, 1.7). Mothers with disabilities were more likely to want another child (1.5), but less likely to intend to have a child (0.5), than were mothers without disabilities. CONCLUSIONS Deepening understanding of the reproductive health desires, needs and challenges of women with disabilities is essential if the highest quality reproductive health services are to be provided for all.